Pengaruh Partisipatif Leadership Terhadap Motivasi Kerja Karyawan Pt. Jayamandiri Gemasejati Cabang Kopo - Ayu Nike Retnowati (LPPM UNIBI, 2020)
In this study, the background is the work motivation of employees at PT. Jayamandiri Gemasejati Kopo branch where there is a decline regarding the goals and objectives of both individuals and organizations, because it requires a process including efforts to develop, motivate, and evaluate all human resources in achieving goals. This study aims to determine the participatory state of leadership and work motivation of employees at PT. Jayamandiri Gemasejati, Kopo branch and the influence. This research uses descriptive method, verification with a quantitative approach. The population used in this study were all employees of PT. Jayamandiri Gemasejati Kopo branch, amounting to 33 respondents using non probability sampling techniques. Based on the results obtained, the participatory leadership condition is in the passablly category and work motivation is in the low category. Based on the results of the determination test, it was found that participatory leadership had an effect of 70.7% on work motivation